Students' and educators' experiences with instructional activities towards critical thinking skills acquisition in a nursing school - Christian Makafui Boso; Anita S. van der Merwe; Janet Gross (Elsevier, 2021)
Graduates of nursing programmes are required to acquire critical thinking (CT) skills in order to provide safe and effective nursing care to patients. To facilitate CT skills of students, it is important to understand the experiences of educators and students regarding their roles, their perspectives on enhancing and inhibiting factors in facilitating CT skills. However, there are limited studies that have explored experiences of nursing students and educators towards CT skills development, albeit with varying focus. The aim of this study was to explore the experiences of nursing students and nurse educators pertaining to instructional activities concerning the acquisition of CT skills of students. Group interviews were used to gather data from 11 nursing students and 4 nurse educators of a nursing programme. The interviews were transcribed verbatim and analysed into themes. The following four key themes emerged from the data: educators' characteristics, students' characteristics, infrastructure (university-wide factors), and continuous quality improvement measures. These themes are useful in helping nursing students, educators, and school managers to understand the experiences of students and educators regarding CT and instructional activities; and consequently, assist the educators and school managers to adopt innovative teaching strategies to guide students to acquire CT skills.